ANALISIS QUALITY FUNCTION DEPLOYMENT UNTUK MENINGKATKAN KUALITAS LAYANAN dan DAYA SAING (STUDI PADA URBANCUT BARBERSHOP SEMARANG) - Drestanta, Raka; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2017)
Urbancut Barbershop is a barbershop located in Semarang. The barbershop business has grown a lot in Semarang, especially in Pleburan, making the competition tighter and causes decline in the number of customers in certain months. In order to overcome this, Urbancut Barbershop has to fulfill customer’s expectation. This research explains about Quality Function Deployment (QFD) implementation and aims to calibrate customer’s expectation and company technique requirement so that Urbancut Barbershop’s operational can match consumer’s expetation.Data in this research is taken through questionnaire surveys for the Manager of Urbancut Barbershop and 50 of their consumers as respondents based on purposive sampling method. this study uses Quality Function Deployment (QFD) to analyze data.The research shows that priority order based on absolute weight of customer’s order that has to be prioritized in increasing the company’s operational power. The research also shows priority order based on absolute weight and technique requirement of relative weight in terms of fixing and increasing service quality of Urbancut Barbershop.